(untitled) (Sciental Journal of Education Humanities and Social Sciences, 2025)
Remittances have emerged as one of the most significant external financial flows for many developing countries, surpassing foreign direct investment and official development assistance in some cases. For Uzbekistan, where labor migration remains a structural feature of the economy, remittances account for a considerable share of GDP and household income. This article examines the relationship between remittances, human capital formation, and sustainable development in Uzbekistan through an international perspective. Drawing on theoretical frameworks of migration and development, as well as global evidence, the study assesses the extent to which remittances contribute to poverty alleviation, education, healthcare, gender empowerment, and long-term economic transformation. The paper highlights both opportunities and risks, including remittance dependency, brain drain, and inequality. By comparing Uzbekistan’s experience with other remittance-dependent economies such as the Philippines, Kyrgyzstan, and Mexico, the article identifies key lessons for policy. The findings suggest that while remittances have positively affected poverty reduction and improved access to health and education services, their contribution to sustainable development is contingent upon effective policies that channel these flows into productive investments and human capital enhancement. The paper concludes with policy recommendations aimed at strengthening Uzbekistan’s development strategy, ensuring that remittances serve as a catalyst for inclusive and sustainable growth.